2006
DOI: 10.1007/s10067-005-1153-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of salmon calcitonin in complex regional pain syndrome (type 1) in addition to physical therapy

Abstract: The aim of the study was to assess the efficacy of salmon calcitonin, which was suggested as effective in the treatment of complex regional pain syndrome type 1 (CRPS 1). Patients who had suffered trauma to their upper extremities and developed CRPS 1 were included into this randomised, controlled single-blind study. The diagnosis was made according to the clinical examination and scintigraphy. The evaluation parameters were: pain [visual analogue scale (VAS)], the angle of dorsiflexion (DF) and palmar flexion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 20 publications
0
27
0
6
Order By: Relevance
“…However, the two placebo-controlled trials of the five in the meta-analysis produced conflicting results. A more recent study found that calcitonin was no more effective than paracetamol in improving pain and function in CRPS over a 2-month period in patients receiving physical therapy following upper limb trauma (Sahin et al, 2006 Level II).…”
Section: Calcitoninmentioning
confidence: 99%
“…However, the two placebo-controlled trials of the five in the meta-analysis produced conflicting results. A more recent study found that calcitonin was no more effective than paracetamol in improving pain and function in CRPS over a 2-month period in patients receiving physical therapy following upper limb trauma (Sahin et al, 2006 Level II).…”
Section: Calcitoninmentioning
confidence: 99%
“…In this condition, calcitonin has also been reported to improve physical performance and lengthen the walking distance [151]. However, in more severe cases of neurogenic compression, the effect of calcitonin was poor [146], and no substantial clinical improvement was obtained by adding nasal calcitonin to physical therapy in patients with complex pain syndrome (type I) [152]. Improvement of pain has also been observed in metastatic tumors with bone localizations [153][154][155], where the decrease of bone resorption activity and consequent reduction of bone erosion may affect the painful symptomatology.…”
Section: Clinical Evidencementioning
confidence: 96%
“…In addition, the subjects were randomized to a two-month regimen of nasal calcitonin or oral paracetamol. At two months, Sahin et al 6 observed no intergroup differences pertaining to pain, range of motion, allodynia, hyperalgesia, and trophic changes.…”
Section: Calcitoninmentioning
confidence: 97%